Imaging-based assessment of corneal graft rejection after penetrating keratoplasty: insights from confocal microscopy and anterior chamber analysis - Lin, Yuan; Liu, Miaomiao; Li, Hanqiao; Fang, Xie; Xie, Zhiwen; Luo, Shunrong; Xiao, Xianwen; Wu, Huping (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to explore the distribution of rejection and visual changes after optical and therapeutic penetrating keratoplasty (PKP) in Southeastern China.MethodsThis retrospective study included 104 patients who underwent either optical or therapeutic PKP between December 2014 and April 2022 at the Xiamen Eye Center. The collected data included demographic characteristics, primary disease, visual acuity, in vivo confocal microscopy (IVCM) findings, and postoperative outcomes. Endothelial inflammation was assessed using IVCM, and anterior chamber paracentesis was performed on patients with recurrent rejection (>2 hospitalizations) for viral and cytokine analyses.ResultsOf 104 eyes (68 men and 36 women; mean age 51.9 ± 12.9 years), 42 received optical PKP and 62 received therapeutic PKP. The mean host bed size was 7.81 ± 0.75 mm, and the graft size was 8.28 ± 0.75 mm. During follow-up, four patients developed secondary glaucoma and one relapsed. A total of 12 patients (2 optical, 10 therapeutic) required repeat PKP and were successfully managed. A larger graft size (>7.8 mm) and therapeutic PKP were identified as significant risk factors for graft rejection, whereas conjunctival congestion, infiltration depth, and femtosecond-assisted PKP were not significantly associated with rejection. Among the 40 cases with recurrent rejection, aqueous fluid analysis revealed viral infection in 20% (3 VZV, 10 HSV, and 7 CMV). Elevated levels of inflammatory cytokines were found in 32 cases, and they responded positively to steroid treatment. However, three cases showed a poor response to the treatment.ConclusionPKP effectively addresses both optical and therapeutic indications; however, larger grafts and therapeutic PKP increase the risk of rejection. Imaging with IVCM and anterior chamber analysis provides valuable diagnostic and prognostic information, supporting individualized management of graft rejection.